Government environmental attention and urban ecosystems metabolic efficiency: Does the digital economy matter - Xiangmin He; Shenrun Yan; Jingyun Miao; Weilin Zeng (PLoS ONE, 2025)
Metabolic efficiency serves as a critical indicator of the operational quality of urban ecosystems. This study utilizes panel data from Chinese cities and applies the spatial Durbin model to examine the impact of government environmental attention (GEA) on the metabolic efficiency of urban ecosystems (UME). The findings indicate that GEA significantly promotes UME and exhibits spatial spillover effects. Moreover, GEA demonstrates notable heterogeneity in its influence on UME. Specifically, it exerts a more pronounced improvement effect in mid-sized and western cities, resource-based cities, and cities with relatively lower levels of economic development. Using the dynamic panel threshold regression model, this study further reveals that GEA has a significant nonlinear impact on UME, with digital economy development serving as the threshold variable. Once the level of digital economy development surpasses the threshold, the role of GEA becomes even more prominent. This research provides valuable decision-making references for developing countries aiming to promote the sustainable development of cities.